(3GSJQGJjLjGJ GdJYde GdEHOGYj (B/s - (3GdefGYj, TeSGf YHO Gddgs ((3YeGf (B- (3GdeedcI GdCQOfjI GdgGTejI (B:s (3OHj (B- [(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3eQcR OjHhfh dJYdje GdJacjQ,s, 2017)
(3jJfGhd cJGH (B"(3GSJQGJjLjGJ GdJYde GdEHOGYj(B.. (3CfTWI hJWHjbGJ YedjI(B" (3hGdPj bGe HJCdjag (B((3TeSGf YHO Gddg GdefGYj(B) (3hGdPj jbY aj MhGdj (B(386) (3UaMI ef GdbWY GdeJhSW, Yf JfejI egGQGJ GdJacjQ GdYdjG GdJj CUHMJ gOaG GSJQGJjLjG aj GdOhd GdeJbOeI, hjMhj GdcJGH Ydi HMhK haUhd PGJ bjeI JQHhjI hJYdjejI, JKQj GdSGMI GdacQjI hGdJQHhjI, hGdHMK GdYdej aj GdeedcI, hjHPd GdeDda eLghOG HGdGgJeGe aj WQM bVGjG JJYdb HCSGSjGJ Ydhe GdJQHjI hebheGJ hESJQGJjLjGJ GdJYde(B.s
(3HHdjhLQGajI (B: (3UaMI (B377-386.s
Keywords: (3GdJYdje ef CLd GdEHOGYs; (3GdEHOGY aj GdJYdjes; (3GdJacjQ GdEHOGYjs -- (3OQGSI hJYdjes